Decentralization and democracy in Iran / Saeid Nouri Neshat - Saeid Nouri, Neshat (2017)
It was only twenty years after the 1979 Revolution that local Islamic councils were legalized and launched everywhere in Iran as part of reforms to strengthen decentralization and enhance people’s participation in policy planning. However, although these councils comprise elected members, they have not been fully institutionalized within the local government system and within Iran’s hierarchy of power. Local councils, therefore, have not led to the greater empowerment of people. This study assesses the decentralization process within the power structure after the Iranian Revolution. The research aims to provide insights into these key questions: how was the structure of the post-revolution decentralization system different from that of the previous regime? Why has the policy of decentralization not led to the sort of devolution that would enable people to participate in decision-making? What are the political obstacles to the empowerment of the people, a professed goal of the postrevolution government? A qualitative research method involving a multiple case study approach is used here. Urban and rural communities were selected for assessment through purposive sampling. Easton’s theory of political system was applied as it provides an effective conceptual framework to examine and explain the data. The results indicate that the post-revolution system is one that can be classified as a filtered democracy. In this type of political system, inputs from society have to pass through filters created by power elites. The feedback loop within society does not connect the inputs to the outputs. Demands from society, therefore, are not the basis for decision-taking at the top level of the political system. Only certain urban-based councils, particularly those in Tehran, showed degrees of power devolution. In Tehran, the councils have moved from beyond their defined legal functions. The whole decentralization process faces a series of political obstacles that cannot be removed until the system reforms its centralized hierarchy of power. There is a tightly controlled hierarchy of government bodies, from the center down to the provinces, townships, districts and villages, in all parts of this filtered democracy. The councils are not institutionalized in the political system. The decentralized councils are only connected to municipalities that are responsible for certain municipal services. These councils are not decision-making organisms, rendering invalid the post-revolution objective of people empowerment.